Intestinal torsion in two killer whales: a pathology study - Lorenzo Pérez, Carla (2024)
Intestinal torsion (volvulus) is a life-threatening clinic-pathological condition that affects humans and many animal species, with very few scientific references in cetaceans, particularly killer whales. Clinical diagnosis is difficult for cetaceans, and treatment is, so far, unrealistic for this species. Etiologies and predisposed risk factors are also a challenge for veterinarians. Therefore, information from dead killer whales is valuable for cetacean medicine and conservation. With this aim, the present final degree work (TDW) shows a pathological study of two cases of intestinal torsion in killer whales (Orcinus orca) kept under human care. Detailed macroscopic and microscopical findings and microbiological results from one of the studied killer whales are presented. A hemodynamic - hemorrhagic - necrotizing - enterotoxigenic – septic shock due to intestinal torsion was finally diagnosed as the cause of death in both killer whales.